The Influence of Cultural, Social And Psychological Factors on Purchase Decision (Toyota Intercom) - Muslimah, Alfani; Khairunisa, Azizah; Putra Wendiq, Rahmadia; Fandu Wijaya, Afdhal (Greenation Publisher & Yayasan Global Research National, 2023)
This study aims to examine whether cultural, social, and psychological factors influence purchase decisions in the study of Toyota Intercom, West Pasaman. The data collection method was taken with a non-probability silencing sample design. The sampling technique was 80 people from a population of 400 employees of Toyota Intercom .. The analytical method used was multiple linear regression using SPSS21. The results obtained were that whether cultural and social had a significant effect on whether cultural, social, psychological factors had a significant effect on buying decisions, and the direct effect of work culture and social was smaller than the indirect effect of on buying decision. The contribution of the independent variable of Culture and Social to the dependent variable of Physchological Factors is 46.1%. While the remaining 53.9% is influenced by other variables outside of this study. The contribution of the independent variable contribution of cultural, social, and psychological factors to the dependent variable of buying decision was 61.7%. While the rest is 38.3% influenced by other variables outside this study.